Intraoperative Management of Adult Patients on Extracorporeal Membrane Oxygenation: An Expert Consensus Statement From the Society of Cardiovascular Anesthesiologists—Part II, Intraoperative Management and Troubleshooting. (15th November 2021) - Mazzeffi, Michael A.; Rao, Vidya K.; Dodd-o, Jeffrey; Del Rio, Jose Mauricio; Hernandez, Antonio; Chung, Mabel; Bardia, Amit; Bauer, Rebecca M.; Meltzer, Joseph S.; Satyapriya, Sree; Rector, Raymond; Ramsay, James G.; et al.
Abstract : In the second part of the Society of Cardiovascular Anesthesiologists Extracorporeal Membrane Oxygenation (ECMO) working group expert consensus statement, venoarterial (VA) and venovenous (VV) ECMO management and troubleshooting in the operating room are discussed. Expert consensus statements are provided about intraoperative monitoring, anesthetic drug dosing, and management of intraoperative problems in VA and VV ECMO patients.